An improved four step commutation process for silicon carbide based matrix converters - Ali, S.; Wolfs, Peter (2016)
© 2016 IEEE. This paper describes an improved matrix converter (MC) commutation process. The paper reviews existing commutation methods including the overlap and dead-band approaches and then two-, three- and four-step commutation processes. Their limitations are discussed and an improved fourstep commutation process is proposed. The paper categorises switches as one or two active devices, or degree of freedom (DOF), implementations. The paper focuses on a two degrees of freedom SiC MOSFET switch for a four by four generalised MC implementation. The commutation process is summarised using two- three- and four-leg state machine diagrams. Experimental results are presented for Si-based MOSFETs and SiC-based MOSFETs switches using the four-step two-leg commutation process.